Nuevos espacios de escucha para voces silenciadas : Åcómo es la experiencia de las integrantes de grupos estudiantiles que acompañan a personas que han sufrido algún tipo de violencia sexual durante la vida universitaria? (2018)
"This study examines the experience of students that conforms groups to support victims of sexual violence in university contexts. Therefore, analyzes the influence of an actor that has not been previously study for contribute to increase the comprehension of sexual violence. In this studied participated 8 members of this students? groups: women, students of university of Bogotá and in an age range between 20 and 24. The information was recollected through the application of a survey and an interview to the participants. After that, the information of the interviews was encoded and contrasted with the results of the survey. The study allows for thinking that the student?s groups respond to an institutional fault in the management of the cases that involves sexual victimizations." --